A Review on Success Factors of Logistic Innovation in Agro-Industry - Yulia M Zai, Yovita; Ampuh Hadiguna, Rika; Afrinaldi, Feri (International Journal of Engineering and Technology, 2018)
Innovation is much required to efficiently manage the logistics system. At the same time, to come up with a successful innovation is also a challenge for the agro-industry. There are many literatures which defined the success factors of logistics innovation. This study investigates the success factors of logistics innovation for agro-industry and determines factors relevant to the business process of agro-industry based on literature published between 2015 and 2018. Through a Systematic Literature Review with fifteen were determined as success factors of logistics innovation in agro-industry, i.e. (1) technology utilization, (2) suistainability, (3) distribution and transportation management, (4) infrastructure, (5) strategic planning, (6) technical support and service architecture, (7) integrated information technology, system, and management, (8) regulation/ policy, (9) logistics cost, (10) collaboration, (11) logistic competence, (12) alliance strategy, (13) continuous improvement, (14) efficiency in business processes, and (15) hunting on positive practices. The Fifteen factors have the same degree of importance and have the same contribution to the successful achievement of logistics innovation.